SOCIAL-ECONOMIC CHARACTERISTICS OF TRADITIONAL FISHERMEN IN NAGARI AIR HAJI KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Nastati, Rosi; Rianto, M.Pd, Slamet; Prari Keslan, Widya (Pendidikan Geografi, 2014)
AbstractsÂ This study aims to obtain data, information and an overview of the characteristics of traditional fishing in Nagari Air Haji Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan in view of: 1) education, 2) health, 3) the fulfillment of basic needs, 4) the level of income, 5) fishery infrastructure. The research method is descriptive. The population in this study whole families of fishermen who reside in the Nagari Air Haji Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan Shore families totaling 336 samples taken penenlitian with proportional random sampling technique with a proportion of 30% that the sample amounted to 58 families of fishermen. The results of the study found that: 1) education of fishermen generally completed SLTP and most have informal education, 2) health condition many traditional fishermen went to health centers, distance to health facilities between 500 m-1 km and the cost of treatment is derived from the cost of his own, never taking multifitamin food, household waste and disposed of at any place where activities mck home alone, 3) traditional subsistence fishermen were able to meet the food needs of the family, frequency of providing basic food 3 times a day, the main staple food and rice is the staple food of complementary foods and vegetables side dishes, 4) the level of income of the average traditional fishing-1.000.000/bulan RP 900,000, 5) traditional fishermen commonly use lift nets.Â